2005
DOI: 10.1007/s11010-005-4817-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the cardioprotective effect of l-cysteine

Abstract: In many tissues the availability of L-cysteine is a rate-limiting factor in glutathione production, though this has yet to be fully tested in heart. This study aimed to test the hypothesis that supplying hearts with 0.5 mM L-cysteine would preserve glutathione levels leading to an increased resistance to ischaemia reperfusion. Left ventricular function was measured in isolated perfused rat hearts before, during and after exposure to 45 min global normothermic ischaemia. Control hearts received Krebs throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Those effects of L-cysteine might have been due to direct scavenging by free radicals or to an improved antioxidative status through the preservation of GSH. 20) In contrast, excessive dietary cysteine is known to cause oxidative stress. 32,33) It has even been reported that extreme doses of sulfur amino acid caused mortality in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those effects of L-cysteine might have been due to direct scavenging by free radicals or to an improved antioxidative status through the preservation of GSH. 20) In contrast, excessive dietary cysteine is known to cause oxidative stress. 32,33) It has even been reported that extreme doses of sulfur amino acid caused mortality in rats.…”
Section: Discussionmentioning
confidence: 99%
“…20) However, it is not yet fully understood whether L-cysteine supplementation has a positive effect on lipid metabolism together with the antioxidative system under normal conditions.…”
mentioning
confidence: 99%
“…This drug is a precursor to the amino acid cysteine which is a rate-limiting factor in glutathione production. Inclusion of cysteine in the perfusate of perfused rat heart has been shown to confer significant cardioprotection and improved preservation of ATP and glutathione (Shackebaei, King, Shukla, & Suleiman, 2005).…”
Section: N-acetylcysteinementioning
confidence: 99%
“…Because of the high reactivity of this thiol, cysteine is able to bind covalently and efficiently ACD by forming stable nontoxic 2-methyl-thiazolidine-4-carboxylic acid compound (Nagasawa et al, 1987;Salaspuro et al, 2006). Cysteine is efficacious to bind ACD derived from alcohol drinking to prevent the possible role of ACD in the pathogenesis of digestive tract cancer (Salaspuro, 2007;Salaspuro et al, 2002Salaspuro et al, , 2006, alcoholic cardiomyopathy, against the chronic toxicity of ACD (Sprince et al, 1974) and also for its antioxidant properties (Shackebaei et al, 2005). Moreover, N-acetyl cysteine, an analogue of the dietary amino acid cysteine attenuates EtOH-induced increased blood pressure and adverse renal vascular changes (Vasdev et al, 1995).…”
mentioning
confidence: 99%